Tata Busana Adat Bali Aga Desa Tenganan Pagringsingan Dan Desa Asak Karangasem - I Ketut Darsana (Institut Seni Indonesia Denpasar, 2007)
This is a report of research findings regarding the lore of traditional clothing/costume in Bali Aga village in terms of its form, function, and meaning, along with its transformation in dance creativity. This is recently developed in the villages of Tenganan Pegringsingan and Asak Karangasem, where the art is inherited from one generation to another generation. The developed form of clothing in the traditional village of Bali Aga is distinctively unique, i.e. the featuring form is stimulated by the mutual support between the function and the meaning. In addition to featuring the aesthetic form, the clothing lore also reflects the meaning. This is possible due to the fact that the selected form does not only cater to the aesthetic deliberation, but he content reflects worthy and interesting symbolic values.